Foreign output shock in small open economies : a welfare evaluation of monetary policy regimes - Alba, Joseph Dennis (2020)
We examine the impact of negative foreign output shocks, which entail negative demand side effects by lowering exports and positive supply side effects by lowering oil prices, on the welfare of non-oil producing, small open economies under five exchange rate and monetary policy regimes. We use a dynamic stochastic general equilibrium model with parameter values calibrated for Hong Kong, Israel, Singapore, South Korea and Taiwan. We find that welfare levels among the five policy regimes depend on the economy's share of oil imports in world oil consumption. Hong Kong, Singapore and Israel, which have smaller shares, maximize welfare under the Taylor rule, which targets both CPI inflation and real output. South Korea, with higher shares, and Taiwan, with more rigid prices, maximize welfare under real output targeting. CPI inflation targeting, nominal output growth targeting and fixed exchange rate regimes generate lower welfare. However, optimal monetary policy, which generates the highest welfare, gives greater weight on real output than CPI inflation.